2014
DOI: 10.1136/heartjnl-2014-306110
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic findings in 2261 peri-pubertal athletes with or without inverted T waves at electrocardiogram

Abstract: In this broad population of peri-pubertal male athletes, TWI in anterior leads was associated with mild cardiac disease in 4.8% of cases, while TWI in infero-lateral leads revealed HCM and LV hypertrophy in 60% of cases. ECG identified all cases of HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
(46 reference statements)
1
31
0
1
Order By: Relevance
“…As such, this paper by Calo et al 8 advances our understanding of TWI in athletes in several ways. First, their data demonstrate that TWI confined to the anterior leads are common among young Caucasian athletes and are highly unlikely to reflect clinically relevant disease.…”
Section: Novel Insights Into Athletic T-wave Inversionsmentioning
confidence: 86%
See 2 more Smart Citations
“…As such, this paper by Calo et al 8 advances our understanding of TWI in athletes in several ways. First, their data demonstrate that TWI confined to the anterior leads are common among young Caucasian athletes and are highly unlikely to reflect clinically relevant disease.…”
Section: Novel Insights Into Athletic T-wave Inversionsmentioning
confidence: 86%
“…Calo et al 8 present data that provide some novel insights into athletic TWI. This investigative group from Italy examined the incidence, 12-lead territorial distribution, and echocardiographic correlates of TWI in a sizeable cohort (n=2261) of adolescent male football athletes.…”
Section: Novel Insights Into Athletic T-wave Inversionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes of Afro-Caribbean origin, who comprised 20% of Sheikh's study group, are more likely to present TWI than are Caucasians [10,27]. Many publications based on additional tests such as echocardiography and cardiac magnetic resonance revealed that TWI is closely associated with cardiac diseases, particularly with HCM [28][29][30][31]. In the cited paper, the TWI was present in 97% of athletes with diagnosed HCM [10].…”
Section: Discussionmentioning
confidence: 96%
“…This cut-off did not improve diagnostic ability compared with the presence of negative T-wave in more than 2 contiguous ECG leads; this was due to a high Pearson correlation (0.76, p b 0.01) between these two parameters. Therefore, spatial QRS-T angle seems to be a useful quantitative value, but as a binary parameter it is less useful to establish a differential diagnosis with a likelihood ratio similar to the presence of TWI in HCM [22] or to the localization of the TWI in inferior-lateral leads [23].…”
Section: Discussionmentioning
confidence: 98%